Fatigue predictions for flexible marine propellers using FSI analysis considering Euler force in the rotating frame. (January 2021) - Joe, Beom-Jin; Choi, Yo-Seb; Jang, Won-Seok; Hong, Suk-Yoon; Song, Jee-Hun; Kwon, Hyun-Wung
Abstract: Analysis of flexible marine propellers in terms of their structural response and stress is the key to accurate fatigue prediction. At present, finite element method (FEM) analyses of flexible propellers have been performed as a part of the fluid–structure interaction (FSI) analysis using a numerical method for the flexible structures, which is identical to that used for their rigid counterparts. In this study, the Euler force in a rotating frame is employed as an additional external force on the blades of the marine propeller during the FSI analysis. The Euler force is an inertial force component in the rotating frame due to angular acceleration. Acceleration of the rotating frame arises from large deformations of the propeller due to its flexible characteristics. The angular acceleration of the propeller is obtained for each time step, and the resulting Euler force is accounted for as a body force. The FSI analysis results are compared to experimental results in terms of the structural response, stress, and fatigue. It is clear that the Euler force has a major effect on the fatigue characteristics of the propeller because it amplifies the main response components. In conclusion, incorporating the Euler force in FSI analyses of flexible marine propellers is necessary for adequate prediction of the propeller fatigue. Highlights: Former FSI analysis of flexible propellers assumed constant angular velocity. Large deformations of the propeller lead to unignorable rotational acceleration. Rotational acceleration was considered via Euler force in the FSI analysis. Euler force amplifies the major response components of the structure. Amplification of the response leads to increase of fatigue probability.